Sahelian techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Soil and crop growth variability in the Sahel (Information Bulletin 49) by J Brouwer and J Bouma 1997 41 pp